Draw like an artist : 100 faces and figures : step-by-step realistic line drawing : a sourcebook for aspiring artists and designers /: 100 faces and figures : step-by-step realistic line drawing : a sourcebook for aspiring artists and designers. ([2019]) - Legaspi, Chris
No abstract available